2001
DOI: 10.1177/008124630103100208
|View full text |Cite
|
Sign up to set email alerts
|

Traditional African1 Beliefs and Customs: Implications for AIDS Education and Prevention in Africa

Abstract: Many Western-based AIDS education and prevention programmes have failed dismally in Africa and they may only succeed if traditional African beliefs and customs are taken into account. This article discusses relevant aspects of the traditional African worldview by explaining what health, sickness and sexuality mean in traditional Africa. Traditional African perceptions of causes of illness (including AIDS), perceptions of sexuality, and cultural beliefs inhibiting the usage of condoms are described in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 17 publications
1
46
1
1
Order By: Relevance
“…Further, more urban than non-urban students believed that "One can get HIV through witchcraft". This finding is contrary to what [13] noted that witchcraft is believed to be the causal agent in HIV transmission and AIDS in many African countries, especially among rural poor or least-educated people. However, adolescents undergoing socio-cultural change in urban contexts may increasingly recur to witchcraft beliefs [14].…”
Section: Discussioncontrasting
confidence: 99%
“…Further, more urban than non-urban students believed that "One can get HIV through witchcraft". This finding is contrary to what [13] noted that witchcraft is believed to be the causal agent in HIV transmission and AIDS in many African countries, especially among rural poor or least-educated people. However, adolescents undergoing socio-cultural change in urban contexts may increasingly recur to witchcraft beliefs [14].…”
Section: Discussioncontrasting
confidence: 99%
“…Given this context and drawing on other studies (e.g. Van Dyk 2001;Verheij 2007;Sigamoney 2009), the suggestion is that, instead of trying to eliminate traditional beliefs and practices, HIV/AIDS education and prevention strategies should accept and respect these forms of representation as long as they are not harmful to the people's health. However, when traditional practices are perceived to contribute to the spread of HIV/AIDS, effort should be made in order to make them safer, as is the case of widow cleansing.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Traditional African healing systems exist in parallel with Western healing approaches (Van Dyk, 2000). The integration of these concepts has been promoted (Moodley & West, 2005), and interest in indigenous African healing systems has been established (Madu, 2003;Mpofu et al, 2011).…”
Section: Culture In Therapeutic Interventions In South Africamentioning
confidence: 99%
“…CWFs were conscious of culture-specific belief systems (Eagle, 2004) and their own cross-cultural competences (Hickson & Christie, 1989). They recognised a connection between CW and cross-cultural expectations and belief and healing systems (Van Dyk, 2000), and therefore promoted a cross-cultural CW approach: combining family therapeutic and traditional healing approaches (Moodley & West, 2005).The findings showed that CWFs identified 'the soul' as an important theme (Cohen, 2006;Van Kampenhout, 2003), and that conscience, belonging, balance and hierarchy, and existence were concepts that simultaneously influenced and derived from the principles of CW (Cohen, 2006). Illness, symptoms, victimhood and perpetratorhood, fostering, adoption and couple problems (Hausner, 2008;Ruppert, 2000;Weber, 1994) also numbered among the important themes in South African CW.…”
mentioning
confidence: 99%